2022
DOI: 10.3390/vaccines10071083
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transfer of Maternal Antibody against SARS-CoV-2 and Its Influencing Factors: A Review

Abstract: Since the beginning of the coronavirus disease 2019 (COVID-19) outbreak, the disease has rapidly become a global threat. The constant emergence of new variants has increased the difficulty of controlling this disease. Vaccination is still considered the most effective method to prevent COVID-19. Vaccination has expanded to include children aged 3–17 years old, and some countries have lowered the age of vaccination to 6 months (for example, the United States). However, children under 3 years old are still not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The degree of maternal protection through placental antibody transfer is most likely dependent on the maternal antibody concentration. In some studies, transplacental transfer of antibodies begins in the second trimester although it was more efficient in the third trimester [44].…”
Section: Preventionmentioning
confidence: 99%
“…The degree of maternal protection through placental antibody transfer is most likely dependent on the maternal antibody concentration. In some studies, transplacental transfer of antibodies begins in the second trimester although it was more efficient in the third trimester [44].…”
Section: Preventionmentioning
confidence: 99%
“…In addition, we also analyzed patients that received up to four doses, which allowed us to compare the different vaccination schemes. Previously published studies showed results regarding BNT162b2, mRNA1273, and Ad26.COV2.S [ 35 , 36 ]. Many countries in the world have limited access to these types of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this effect could also be achieved with the mRNA vaccine or not is yet to be shown. However, it appears plausible since mRNA vaccination of pregnant women against COVID‐19 has been shown to lead to transplacental transfer of neutralizing antibodies (but no transfer of mRNA vaccine compounds) protecting SARS‐CoV‐2 during early infancy 205,206 …”
Section: Clinical Progress Of Mrna Candidates Beyond Covid‐19mentioning
confidence: 99%